Treatment of Waste Water from Complex Organic Substances - B. S. Ksenofontov; A. S. Kozodayev; R. A. Taranov; M. S. Vinogradov (Novel Perspectives of Geography, Environment and Earth Sciences Vol. 5, 2023)
This paper covers the issue of extraction of polycyclic hydrocarbons from waste water by using physical and chemical technology including the use of flotation, sedimentation, filtration, adsorption, ozonation. The use of this technology makes it possible to significantly reduce the concentration of hazardous substances such as benzapyrene in the waste water. Under certain conditions of wastewater treatment using physical and chemical technology the concentration of benzapyrene does not exceed the regulatory values. The results of the studies showed that the microflora of wastewater contaminated with Polycyclic aromatic hydrocarbons (PAHs) is capable of destroying PAHs, including BP. Prospects for the use of chemoflotocombines for the treatment of waste water containing complex organic substances are considered.